Place-Making in urbanen Diskursen - Warnke, Ingo H.; Busse, Beatrix (Diskursmuster, 2014)
Urban spaces are configurations of discursively generated places. This volume of essays in discursively oriented urban research features a broad range of interdisciplinary perspectives. A focus is placed on practices and resources for analyzing urban spaces, as well as on communicative markers of urban identity. The book reveals urban linguistics as an emerging interdisciplinary discipline for the study of place-making processes in urban spaces
Beitr. teilw. dt., teilw. engl
Keywords: Aufsatzsammlung; Diskurs; Urbanität; Aneignung; Öffentlicher Raum; Stadt